Material recovery from electronic waste using pyrolysis: Emissions measurements and risk assessment. Issue 1 (February 2021) - Sahle-Demessie, Endalkachew; Mezgebe, Bineyam; Dietrich, Joshua; Shan, Yonggui; Harmon, Stephen; Lee, Chun C.
Abstract: Electronic waste (e-waste) generation has been growing in volume worldwide, and the diversity of its material composition is increasing. Sustainable management of this material is critical to achieving a circular-economy and minimizing environmental and public health risks. This study's objective was to investigate the use of pyrolysis as a possible technique to recover valuable materials and energy from different components of e-waste as an alternative approach for limiting their disposal to landfills. The study includes investigating the potential environmental impact of thermal processing of e-waste. The mass loss and change in e-waste chemicals during pyrolysis were also considered. The energy recovery from pyrolysis was made in a horizontal tube furnace under anoxic and isothermal conditions of selected temperatures of 300 °C, 400 °C, and 500 °C. Critical metals that include the rare earth elements and other metals (such as In, Co, Li) and valuable metals (Au, Ag, Pt group) were recovered from electronic components. Pyrolysis produced liquid and gas mixtures of organic compounds that can be used as fuels. Still, the process also emitted particulate matter and semi-volatile organic products, and the remaining ash contained leachable pollutants. Furthermore, toxicity characteristics leaching procedure (TCLP) of e-waste and partly oxidized products were conducted to measure the levels of pollutants leached before and after pyrolysis at selected temperatures. TCLP result revealed the presence of heavy metals like As, Cr, Cd, and Pd. Lead was found at 160 mg/L in PCBs leachate, which exceeded the toxicity characteristics (TC) limit of 5 mg/L. Liquid sample analysis from TCLP also showed the presence of C10 –C19 components, including benzene. This study's results contribute to the development of practical recycling alternative approaches that could help reduce health risks and environmental problems and recover materials from e-waste. These results will also help assess the hazard risks that workers are exposed to semi-formal recycling centers. Graphical Abstract: ga1 Highlights: Pyrolysis recovers materials and energy from electronic waste, achieving a circular economy. Toxic compounds, including PAHs, VOCs, and particulate matter, emitted from e-waste pyrolysis. Liquid fraction of pyrolysis residue contained metals and PAHs causing water and soil pollution. Toxicity characterization leaching procedure revealed heavy metal could be released. Exposure to harmful compounds from informal recycling causes health risks to workers and the public.